Public accountant professional skepticism behavior in improving audit quality: A path analysis - Adhikara, M. F. Arrozi; Widodo, Agung Mulyo (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2023)
This study investigates the relationship between behavioral observation responses, namely accountability, due professional care, and professional skepticism, and their collective influence on audit quality within public accounting firms. By highlighting the mediating role of professional skepticism, our study offers a model that integrates cognitive dissonance theory with attribution theory, thereby advancing understanding in the field. Furthermore, this study employs a one-shot study approach with individual auditors as the unit of analysis. Data was collected through surveys administered to auditors working in public accounting firms registered with The Indonesian Institute of Certified Public Accountants in Jakarta. The sample comprised 123 auditors selected via Stratified Random Sampling. Path analysis using the AMOS program was employed for data analysis. The results indicate that when auditors feel a sense of accountability and exercise due professional care, they are more inclined to approach their work with heightened skepticism, positively influencing audit quality. This suggests that accountability and due professional care serve as catalysts for fostering a critical mindset among auditors. Consequently, the combined impact of these factors, along with professional skepticism, significantly contributes to enhancing audit quality, highlighting the interconnectedness of these elements in driving effective auditing practices.